Optimization of Organic Mulch Sheet Compositions in Chili (Capsicum annum L.) Cultivation: Effect on the Growth and Yield: Optimization of organic mulch sheet formulation in chili cultivation - Aniek Iriany; Faridlotul Hasanah; Atiek Iriany; Febriana Budi Lestari (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Climate change causes low production of most vegetables throughout the world by reducing the quality and quantity of yield. Mitigation of the negative impact of climate change on plant productivity must be emphasized in the development of production systems to improve the efficiency of water use, including mulch. Organic mulch sheet (OMS) is an alternative biodegradable mulch made from abundant renewable materials. This study aimed to understand the influence of OMS application on the growth and yield of chili compared to plastic mulch and to optimize the compositions of OMS made from water hyacinth, coconut fiber, and manure for improving the growth and yield of chili. This study was carried out using a simple randomized complete block design with two controls (without mulch (P0) and plastic mulch (P0M)) and five treatments of OMS compositions (the percentage of water hyacinth, coconut coir, and manure) labeled as PO1 (70:20:10), PO2 (60:30:10), PO3 (50:40:10), PO4 (40:50:10) and PO5 (30:60:10). All tested OMS compositions in this study showed insignificantly growth and yield variables of chili compared to the plastic mulch. Optimum OMS composition for yield variables obtained at 59.39% water hyacinth and 0% coconut coir based on response optimizer using response surface analysis. Insignificant different growth and yield produced from OMS and plastic mulch application indicated that all tested OMS compositions, with biodegradable and eco-friendly properties, can be used to substitute for plastic mulch in chili cultivation.